Calamity in Qur'anic Perspective: an Examination of Asy-Syarawi's Tafsir and its Relevance in The Modern Era - Abror, Wahyu; Junaidi, Junaidi (JURNAL AT-TURAS, 2024)
This study aims to explore Asy-Sya’rawi's view of calamity as a form of test, warning, or Allah's compassion for his servants, as well as how human responses should ideally be formed based on Qur'anic values. This research uses a qualitative-descriptive method with text analysis on the tafsir of Asy-Sya’rawi's, a prominent mufassir known for his in-depth approach to the meanings of the Al-Qur'an. The results show that Asy-Syarawi's interpretation offers a holistic explanation of calamity, which is not only seen as a negative event but also as a means of introspection and spiritual quality improvement. In the modern era, this concept is relevant to building a resilient attitude, maintaining emotional balance, and strengthening social solidarity in the midst of various challenges such as natural disasters, pandemics, and global crises. This study also underlines the importance of implementing Qur'anic values in dealing with disasters, including patience, tawakal, and optimism. Thus, Asy-Syarawi's tafsir makes a significant contribution in offering a Qur'anic perspective that is contextual and applicable to dealing with disasters in the modern era. This research provides new insights by highlighting the understanding of calamity through Asy-Syarawi's interpretation which emphasises that calamity is not only a test or punishment, but also a form of God's love to educate humans. Different from previous studies that often focus on theological or social aspects separately, this research combines both to provide a more complete view. Tafsir Asy-Syarawi's emphasises the importance of patience, tawakkala and introspection in dealing with disasters, as well as their relevance in the modern era in overcoming challenges such as pandemics, natural disasters and social crises. This research offers practical Qur'anic-based solutions to help individuals and communities face disasters with a more resilient and optimistic attitude.